2022
DOI: 10.1136/bmjopen-2022-061011
|View full text |Cite
|
Sign up to set email alerts
|

Integrated care for older people based on information and communication technology: a scoping review protocol

Abstract: IntroductionIntegrated care is an effective means of coping with the increasingly complex healthcare needs of elderly and alleviating pressure on national pension services. WHO regards integrated care as a method of providing high-quality healthcare and advocates integrated care based on digital technology. Against the backdrop of the COVID-19 pandemic, information and communication technology (ICT) has become a facilitator for the successful implementation of integrated care by providing a platform for inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This study was conducted following the framework of a scoping review developed by Arksey and O’malley [ 11 ] and further updated by Levac et al [ 12 ], and the study protocol has been published in the BMJ Open [ 13 ]. We followed the JBI evidence synthesis manual [ 14 ] and the PRISMA-ScR checklist [ 15 ] to report the scoping review results.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted following the framework of a scoping review developed by Arksey and O’malley [ 11 ] and further updated by Levac et al [ 12 ], and the study protocol has been published in the BMJ Open [ 13 ]. We followed the JBI evidence synthesis manual [ 14 ] and the PRISMA-ScR checklist [ 15 ] to report the scoping review results.…”
Section: Methodsmentioning
confidence: 99%
“…A preliminary search of PubMed returned some systematic reviews on facilitators of and barriers to ICC [6,8,11,18] as well as a handful of scoping reviews on DICC in the primary health care system and for specific disease groups [19][20][21][22][23][24]. However, no current or ongoing PROSPERO-registered systematic or scoping review on our research aim was identified in previous primary and review studies.…”
Section: Overviewmentioning
confidence: 99%
“…A descriptive analysis of articles with quantitative, qualitative, and mixed-method research designs found positive impacts on quality of life, caregiver burden, and primary care resource utilization among older adults, but the validity assessments were not as robust as hoped. Heterogeneity was high, and 60.5% of the included studies were empirical studies, necessitating systematic evaluation to further validate their effectiveness (13). In addition, existing studies have focused on the effectiveness of preventive integrated care for frail older adults in the community (14), the core components and impact of nurseled models of integrated care for older adults at home (15), and systematic evaluations of service providers' perceptions of integrated care for frail older adults (16).…”
Section: Introductionmentioning
confidence: 99%